THE ROLE OF COMMUNITY GROUPS CONCERNED WITH CORRECTIONAL CARE IN EMPOWERING CORRECTIONAL CLIENTS THROUGH JOB TRAINING AT MR. KUMIS BICYCLE REPAIR SHOP - Dandi Prasetiyo Kusuma Aji; Muhammad Ali Equatora (Journal of Management Small and Medium Enterprises (SMEs), 2026)
This study highlights the importance of fostering independence and empowerment among correctional clients in Indonesia, particularly in response to high crime rates associated with low education levels and unstable employment. The empowerment process is implemented through vocational training at the Pak Kumis Bicycle Workshop under the supervision of the Purwokerto Probation Board. Using a descriptive qualitative case study approach, data were collected through in-depth interviews, observations, and documentation involving clients, correctional officers, members of the Pokmas Lipas group, and clients’ families. The findings show that Pokmas Lipas plays a significant role in supporting clients by providing technical skills, psychosocial encouragement, and the development of positive work attitudes. As a result, clients demonstrate improved competence, confidence, discipline, and readiness to live independently after completing their correctional programs. The program also contributes to faster and smoother social reintegration into the community. However, several challenges remain, including inconsistent discipline among clients, limited training facilities, unclear legal status of Pokmas Lipas, and low community involvement. Overall, the study concludes that vocational training through Pokmas Lipas is highly beneficial in strengthening the independence and skills of correctional clients, although improvements in resources, institutional support, and community acceptance are still needed to optimize its impact. Keywords: Correctional Clients; Empowerment; Job Training; Social Reintegration